PENGARUH RISIKO OPERASIONAL DAN RISIKO KREDIT TERHADAP PROFITABILITAS PADA PERUSAHAAN BANK UMUM SYARIAH YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Elen Separingga; Wirman . (Universitas Gorontalo, 2022)
A banking company is one company that always tries to control risk and even avoid risks, both internal and external risks that occur in an organization or business entity. The purpose of this study was to determine the effect either simultaneously or partially between operational risk (BOPO) and credit risk (NPF) on profitability (ROA) at Islamic Commercial Banks for the 2016-2020 period. The sample used in this research is 14 Islamic banking companies. The technique used for sampling is saturated sampling. The analytical method used is multiple linear regression using the SPSS program. The results of the study that simultaneously operational risk (BOPO) and credit risk (NPF) affect the profitability (ROA) of Islamic Commercial Banks for the 2016-2020 period. Partially, the results of the research on the operational risk variable (BOPO) have a negative effect on profitability (ROA). Partially, the results of the research on the credit risk variable (NPF) have a significant negative effect on profitability (ROA) at Islamic Commercial Banks for the 2016-2020 period.